PEMBERLAKUKAN PENGARUH PAJAK PERTAMBAHAN NILAI TERHADAP TRANSAKSI UMKM E-COMMERCE (Implementation Of The Influence Of Value Added Tax On E-Commerce Msme Transactions) - Leni Hartati; Adriani Gunawan; RR. Ella Evrita (Penerbit Goodwood, 2024)
Purpose: To describe and explain the effect of Value Added Tax on MSME E-Commerce transactions. Research Methodology: The research approach used is descriptive qualitative and the type of research is library research. Results: (1) Technological developments have positive and negative impacts for business people and buyers who have the option of shopping online without having to see them in person. (2) The potential for PNN revenue from e-commerce transactions is very high. (3) Barriers to VAT collection for e-commerce transactions are due to low awareness of business actors, weak law enforcement, and the absence of special regulations. (4) The VAT revenue contribution from e-commerce transactions in Indonesia has the potential for very significant results. Limitations: The limitations of this research are as follows: (1) the variables used are limited to the Implementation of the Effects of Value Added Tax; (2) this research is still in narrative form; and (3) this research only uses literature study as the method. Contribution: This research is expected to provide knowledge to readers regarding the Effect of Value Added Tax on E-Commerce MSME Transactions How to cite: Hartati, L., Gunawan, A., & Evrita, R. E. (2024). Pemberlakukan Pengaruh Pajak Pertambahan Nilai Terhadap Transaksi Umkm E-Commerce. Studi Akuntansi, Keuangan, dan Manajemen.